Upaya International Labour Organization (ILO)-IPEC Melalui INDUS Project Dalam Menanggulangi Pekerja Anak di Sektor Industri di India Tahun 2003-2007 - Dwiyutiari.K, Sagung; Priadarsini, Ni Wayan Rainy; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2017)
ABSTRACT                     Human rights violations will be increased with the exploitation and the existence of child labor. India is one country that still have to face the existence of child labor that is quite high, especially in industry. ILO as an international organization dealing with labor issues participate in helping the government to tackle child labor in India which IPEC. Through IPEC, ILO developed a program INDUS Project which is an initial program to assist the Government of India to tackle child labor in the industrial sector in India. This study discusses the efforts of ILO-IPEC through INDUS Project to tackle child labor in India. ILO as an international organization has as its efforts through technical cooperation, research and information and education and training with the locus of time from 2003 to 2007 that are period time of execution of ILO-IPEC program in India.   Keywords : ILO-IPEC, INDUS Project, Child Labour in industry, India